Heterogeneous Catalytic Activity of Platinum Nanoparticles Hosted in Mesoporous Silica Thin Films Modified with Polyelectrolyte Brushes - Rafti, Matias (2013)
Platinum nanoparticles of 3 nm diameter were included in mesoporous silica thin films by controlling the mesopore surface charge with a short polymer brush. This metal-polymer-mesopore nanocomposite presents high catalytic activity toward ammonia oxidation at low temperatures with 4.5% weight platinum loading. An anomalous partial selectivity toward nitrous oxide is observed for the first time, which can be traced back to the synergy of the particles and modified surface. This effect opens a path toward the design of nanocomposite catalysts with highly controlled environments, in which the size- and function-controlled cavities can be tuned in order to lower the reaction barriers.